Analysis of the Implementation of the Independent Curriculum in Elementary Schools in Indonesia - Muhammad Fuadi; Teuku Zulfikar; Sehat Ihsan Shadiqin (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This research is a systematic literature review on implementing the Independent Curriculum in Elementary Schools in Indonesia. The method used in this study is qualitative, with data collection techniques using the library research method. The results of this systematic literature review research: The implementation of the Independent Curriculum was introduced to provide flexibility to schools in designing curricula that align with local needs and student development. In its implementation, the Pancasila student profile strengthening project is a co-curricular activity and does not need to be mapped to achieve Learning Outcomes. Then, the principles of the Pancasila student profile strengthening project are holistic, contextual, student-centered, and exploratory.